Formation of indium tin oxide transparent electrodes by magnetron sputtering for II‐VI compound semiconductor optical devices on InP substrates. Issue 7 (31st March 2014) - Shiraishi, Tomohiro; Nomura, Ichirou; Murakami, Keisuke; Takamatsu, Shingo; Kobayashi, Toshiki; Kishino, Katsumi
Abstract: Indium tin oxide (ITO) transparent electrodes formed on II‐VI compound semiconductor optical devices on InP substrates were characterized. Two kinds of ZnCdSe/BeZnTe p‐n diode devices with a different p‐contact layer (i.e., p‐ZnTe and p‐ZnSeTe layers) were prepared to investigate more suitable p‐contact material for ITO electrodes on the II‐VI devices. Thin ITO layers were deposited on the devices by magnetron sputtering. From injection current density versus applied voltage (J‐V) characteristics, the turn‐on voltage of the ZnTe contact device was found to be lower than that of the ZnSeTe contact device by about 2 V. The J‐V characteristic of the ZnTe device was comparable to that of the device with Au electrodes on the p‐contact instead of ITO. Using ITO electrodes, ZnCdSe/BeZnTe erlattice photovoltaic devices with ZnTe and ZnSeTe p‐contact layers were fabricated. The devices were characterized under 1.5 AM illumination at room temperature. The J‐V characteristics showed that the device performances of the ZnTe contact device were almost erior to those of the ZnSeTe device. Open‐circuit voltage, short‐circuit current density, fill factor, and maximum conversion efficiency of the ZnTe device were 0.90 V, 4.7 A/cm 2, 0.35, and 1.5%, respectively. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)